Genetic screening for macular dystrophies in patients clinically diagnosed with dry age‐related macular degeneration. Issue 6 (15th October 2018) - Kersten, Eveline; Geerlings, Maartje J.; Pauper, Marc; Corominas, Jordi; Bakker, Bjorn; Altay, Lebriz; Fauser, Sascha; de Jong, Eiko K.; Hoyng, Carel B.; den Hollander, Anneke I.
Abstract : It can be clinically challenging to distinguish dry age‐related macular degeneration (AMD) from AMD‐mimicking dystrophies, and sometimes misdiagnosis occurs. With upcoming therapies for dry AMD it is important to exclude patients with a different retinal disease from clinical trials. In this study we evaluated the occurrence of AMD‐mimicking dystrophies in an AMD cohort. Whole‐exome sequencing (WES) was performed in 218 patients with intermediate AMD or geographic atrophy secondary to AMD and 133 control individuals. WES data was analyzed for rare variants in 19 genes associated with autosomal dominant and recessive macular dystrophies mimicking AMD. In three (1.4%) of 218 cases we identified a pathogenic heterozygous variant ( PRPH2 c.424C > T; p.R142W) causal for autosomal dominant central areolar choroidal dystrophy (CACD). Phenotypically, these patients all presented with geographic atrophy. In 12 (5.5%) of 218 cases we identified a heterozygous variant of unknown clinical significance, but predicted to be highly deleterious, in genes previously associated with autosomal dominant macular dystrophies. The distinction between AMD and AMD‐mimicking dystrophies, such as CACD, can be challenging based on fundus examination alone. Genetic screening for genes associated with macular dystrophies, especially PRPH2, can be beneficial to help identify AMD‐mimicking dystrophies. Abstract :